Central Actions of 3α,5α-THP Involving NMDA and GABAA Receptors Regulate Affective and Sexual Behavior of Female Rats - Frye, Cheryl A.; Qrareya, Alaa; Llaneza, Danielle C.; Paris, Jason J. (Frontiers in Behavioral Neuroscience, 2020)
The neurosteroid, 5α-pregnan-3α-ol-20-one (known as “allopregnanolone” or 3α,5α-THP), is produced in the midbrain ventral tegmental area (VTA), independent of peripheral sources of progestogens, where it has potential actions at N-methyl-D-aspartate (NMDA) and GABA(A) receptors to facilitate rodent sexual behavior. Progestogens can also have anti-anxiety effects, but whether these involve actions of centrally-derived 3α,5α-THP or these receptors to support reproductively-relevant behavior is not well understood. We investigated the extent to which 3α,5α-THP’s actions via NMDA and/or GABAA receptors in the midbrain VTA influence reproductive behaviors. Estradiol-primed, ovariectomized/adrenalectomized (OVX/ADX) rats received midbrain VTA infusions of vehicle, a NMDA receptor blocker (MK-801; 200 ng), or a GABA(A) receptor blocker (bicuculline; 100 ng) followed by a second infusion of vehicle or 3α,5α-THP (100 ng). Reproductively-relevant behaviors were assessed: sexual (paced mating), anxiety-like (elevated plus maze), and social (partner preference, social interaction) behavior. Compared to vehicle, intra-VTA infusions of MK-801 exerted anxiolytic-like effects on elevated plus maze behavior and enhanced lordosis. Unlike prior observations in gonadally-intact rats, intra-VTA bicuculline had no effect on the behavior of OVX/ADX rats (likely due to a floor effect). Subsequent infusions of 3α,5α-THP reversed effects on lordosis and infusions of bicuculline inhibited 3α,5α-THP-facilitated lordosis. Thus, NMDA and GABA(A) receptors may act as mediators for reproductive behavioral effects of 3α,5α-THP in the midbrain VTA.